Mental Illness, Madness, Mental Instability and Psychological Issues: A Study of Jane Ayre and The Bell Jar - Parya Kiasat (International Journal of Practical and Pedagogical Issues in English Education)
The study investigates the two novels of Jane Ayre and The Bell Jar, the aspects focus on the psychological matters. These matters are like mental instability and behavioural instability, also the madness. The forms of mental illnesses are many, the ones those are known commonly are linked to women as long as these women are not obedient. The mental instability occurs to several reasons and these reasons are mostly through the life of the women who face such conditions. The reasons are like the imprisonment of women and being locked. The other aspect is the role of the psychological pressure women suffer of and these psychological pressures are made of forms those are different.